2015
DOI: 10.1590/s0034-8910.2015049005352
|View full text |Cite
|
Sign up to set email alerts
|

Access to continued-use medication among older adults, Brazil

Abstract: OBJECTIVE To determine the prevalence and associated access factors for all continued-use prescription drugs and the ways in which they can be obtained.METHODS Data was obtained from the 2008 Household National Survey. The sample comprised 27,333 individuals above 60 years who reported that they used continued-use prescription drugs. A descriptive analysis and binary and multiple multinomial logistic regressions were performed.RESULTS 86.0% of the older adults had access to all the medication they needed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
1
15
0
5
Order By: Relevance
“…Study with senior population in Brazil who reported long-term use of medicines showed prevalence of full access of 86.0% 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Study with senior population in Brazil who reported long-term use of medicines showed prevalence of full access of 86.0% 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, a national survey conducted in 1999 indicated a prevalence of 26.9% 46 ; in Australia, a longitudinal study among people with DM found a prevalence of 21.6% 47 , results close to those found in our study. 18 . Other analytical studies of the NHS estimated that 80.2% of people with DM who were 18 years of age or older used medicines (oral and/or insulin) 26 , of which 57.4% acquired at least one through the BPPP 25 .…”
Section: Discussionmentioning
confidence: 99%
“…By 2014, access to medication in Brazil was only studied indirectly [16][17][18] or in local [19][20][21][22] and regional studies 23 , with different approaches, analytical cuts, methodologies and with little possibility of expansion of results. Results from the Brazilian National Health Survey (NHS) provided information on the use of the Brazilian Popular Pharmacy Program (BPPP) 24 , the prevalence of use of NCD medicines 25 , and the care of people with self-reported DM in Brazil, such as the use of medications (oral or insulin) 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisa Nacional de Saúde (PNS), Brasil, 2013. Fonte: Elaboração própria dos microdados da PNS-2013. Embora os clientes de planos de saúde com maior renda já contem com maior facilidade de acesso aos serviços de saúde, em concordância com o que asseverou Viana et al (2015) sobre o melhor acesso aos sistemas a essa parcela da população, era de esperar que não necessitassem recorrer ao SUS, afinal desembolsam quantias mensais relativamente altas, que podem comprometer boa parte de suas rendas, para contar com um serviço em saúde que oferte melhores cuidados e condições de acesso e utilização. Essa utilização serve para mostrar também que, mesmo entre as classes de maior renda per capita, a potencial utilização da rede de serviços do SUS é uma realidade.…”
Section: Figuraunclassified
“…Há diferenças marcantes segundo a classe socioeconômica, e os extratos da população com menor renda ainda apresentam baixas taxas de utilização de serviços especializados, evidenciando as desigualdades entre as classes. Essas desigualdades no acesso e na utilização, além de ocorrerem entre as pessoas vinculadas e não vinculadas aos planos de saúde, também são perceptíveis entre os clientes dos planos, de tal modo que essa clientela, em um contexto de maior renda, se beneficia de melhor acesso aos cuidados em saúde (Viana et al, 2015).…”
unclassified